damage of the Euschistus heros (f.) (hemiptera: Pentatomidae) to soybean infested at the full seed stage - Scopel, Wanessa (2017)
Abstract: Among pests that attack soybeans, the stink bugs have been featured for potential damage, control difficulties and constants re-infestations. The management os these pest on soybeans should be performed based on the economic threshold level, but the development of new cultivars with different cycle characteristics, growth habits and yield potential, demand that this threshold should be reviewed. The intensity of the damage caused by stink bugs depends, among other factors, on the phenological characteristics of plant, insect and especially the infestation time and the population level present in the culture. A field study was conducted using cages to test the impact of the infestation time of a population of the neotropical brown stink bug, Euschistus heros (F.) (12 adults/m) on soybean seed yield and quality at the full seed stage (R6), in 2011/2012 soybean season, at Passo Fundo, RS. The soybean cultivar used was BMX Apolo RR, with early cycle, 5.5 maturity group and indeterminate growth habit, in completely randomized design with four treatments (infestation time of 0, 7, 14 and 21 consecutive days) and six repetitions. The results indicated that up to 12 stink bugs adults/m (1 insect/plant), during 21 days, did not reduce seed yield and cause no leaf retention. However, in seed production, the same infestation level during 7 days significantly affected the seed viability and vigor.